Shopping with the resale value in mind: A study on second‐hand luxury consumers. (30th September 2019) - Turunen, Linda Lisa Maria; Pöyry, Essi
Abstract: The market for second‐hand luxury products is growing and the variety of available sales channels has increased; consumers can buy second‐hand luxury goods not only from brick‐and‐mortar stores but also from a myriad of both global and local online channels. Arguably, the increase in available sales channels has changed consumers' purchasing behaviour as the roles between sellers and buyers are alternating as one can act as a buyer one day and a seller the next. However, prior research on luxury consumption has mainly focused on brand‐new luxury goods, largely neglecting the consumption of previously‐used luxury products and has not accounted for the multi‐channel shopping environment. The purpose of this paper is to understand how consumers mentally approach the purchase of second‐hand luxury products and what kinds of decision‐making styles they use. The empirical interview data of 22 consumers was analysed by the means of shopping style dimensions that account for both consumer characteristics and external shopping conditions. The interviewees were members of a Facebook buy and sell ‐group focused on luxury products and had recently bought a second‐hand luxury product. All the existing dimensions were evident in the data but an additional dimension was also identified: resale value consciousness. The new dimension emphasizes an investment‐led and price‐quality conscious shopping style but was also found to relate to impulse buying and brand consciousness. The emergence of the dimension is argued to be due to the increase in viable online sales channels for second‐hand luxury products.